Persistent Lung Injury and Prothrombotic State in Long COVID - Xiang, Mengqi; Jing, Haijiao; Wang, Chengyue; Novakovic, Valerie A.; Shi, Jialan (Frontiers in Immunology, 2022)
Lung injury may persist during the recovery period of COVID-19 as shown through imaging, six-minute walk, and lung function tests. The pathophysiological mechanisms leading to long COVID have not been adequately explained. Our aim is to investigate the basis of pulmonary susceptibility during sequelae and the possibility that prothrombotic states may influence long-term pulmonary symptoms of COVID-19. The patient’s lungs remain vulnerable during the recovery stage due to persistent shedding of the virus, the inflammatory environment, the prothrombotic state, and injury and subsequent repair of the blood-air barrier. The transformation of inflammation to proliferation and fibrosis, hypoxia-involved vascular remodeling, vascular endothelial cell damage, phosphatidylserine-involved hypercoagulability, and continuous changes in serological markers all contribute to post-discharge lung injury. Considering the important role of microthrombus and arteriovenous thrombus in the process of pulmonary functional lesions to organic lesions, we further study the possibility that prothrombotic states, including pulmonary vascular endothelial cell activation and hypercoagulability, may affect long-term pulmonary symptoms in long COVID. Early use of combined anticoagulant and antiplatelet therapy is a promising approach to reduce the incidence of pulmonary sequelae. Essentially, early treatment can block the occurrence of thrombotic events. Because impeded pulmonary circulation causes large pressure imbalances over the alveolar membrane leading to the infiltration of plasma into the alveolar cavity, inhibition of thrombotic events can prevent pulmonary hypertension, formation of lung hyaline membranes, and lung consolidation.